PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK DENGAN POLITICAL CONNECTION SEBAGAI VARIABEL MODERASI - Vika Amelia; Widi Dwi Ernawati; M. Arief Setiawan (Jurnal Akuntansi Bisnis dan Humaniora, 2023)
This study aims to examine the effect of firm size, financial distress, and leverage on tax aggressiveness with political connection as a moderating variable. This research is quantitative associative. The population of this study are food and beverage companies listed on the Indonesia Stock Exchange from 2016 to 2020 with a total of 20 companies. The sampling used the purposive sampling method and obtained a sample of 13 companies. The data analysis technique used multiple linear regression and moderated regression analysis (MRA). The results of this study indicate that simultaneously and partially there is no effect between firm size, financial distress, and leverage on tax aggressiveness. A Political connection can moderate the effect of company size and financial distress on tax aggressiveness. The political connection however is not able to moderate the effect of leverage on tax aggressiveness.